Visitors' satisfaction in natural areas: the case of Vinhais biological park - Alves, Diana Rafaela Rocha (2023)
Satisfaction is a widely studied issue in tourism as it provides an understanding of the performance of a tourism destination's offer, highlighting the most important features considered by tourists. The growth in tourism demand in natural areas also makes it an important factor in identifying visitor satisfaction, as sustainable planning of these areas may also rely on knowing the opinion of their visitors. In this context, this study aimed to determine the visitors´ satisfaction with Vinhais Biological Park, located in the northeast of Portugal, during the summer of 2022. A questionnaire consisting of 8 closed-ended questions to identify the socio-demographic profile and overall satisfaction was applied during July and August 2022. Therefore, 251 valid questionnaires were considered for the quantitative data analysis and a final sampling error of 6.13% was assumed. A descriptive statistical analysis was performed to identify the socio-demographic profile and the satisfaction with the resources offered. Four hypotheses were formulated to test the association between socio-demographic profile (age group, gender, nationality, and education level) and overall satisfaction. The χ2 test was used to test the hypotheses assuming a 5% significance level. The main findings showed that the socio-demographic profile of the sample is predominantly male (54.6%), aged between 11 and 40 years (77.6%), of Portuguese nationality (71.3%) and with higher education level (48.6%). Concerning the visit motivation, 61.4% went to the park after visiting the city of Vinhais or the region and nearly half (47%) of the respondents were satisfied. The results of χ2 test revealed no significant association between the socio-demographic profile and overall satisfaction, meaning that none of the hypotheses was supported. Considering the number of visitors received in the park annually, this study's sample can be regarded as a limitation, making the understanding of satisfaction limited to the period of analysis and at a period when the impact of COVID-19 is noticeable. Finally, for future studies, a comparative analysis with other natural parks, both Portuguese and Spanish, is suggested for better monitoring of visitor satisfaction.